AKTIVITAS FUNGISIDA EKSTRAK DAUN SIRIH (Piper betle L.) KULTIVAR BELENG TERHADAP JAMUR Fusarium solani var. coeruleum PENYEBAB PENYAKIT BUSUK KERING PADA UMBI KENTANG (Solanum tuberosum L.) - I Made Subrata (FPMIPA IKIP PGRI Bali, 2016)
Many effort have been done to control the plant disease such as the use of biopetiside. This research was done in order to know inhibitory activity of beatle leaf the cultivar of Beleng extract and its inhibitory mechanism against the growth of F. solani var. coeruleum, that causal agent of dry rot disease on potato tuber. In order to find other alternatives for controlling the disease, Beleng leaf were studied for their bioactivity against F. solani var. coeruleum. The result of the study indicated that the crude extract of Beleng leaf at concentration 0.05%; 0.1%; 0.15%; 0.2%; 0.25%; 0.3% and 0.35% was able to inhibit the radial growth of F. solani var. coeruleum on Potato Dextrose Agar (PDA) medium. The variation of crude extract concentration was found to influence the fungal growth of potato tuber on PD Broth medium. In addition, the crude extract of Beleng leaf was able to inhibit the spore germination and spore formation of F. solani var. coeruleum on PD Broth medium. The fractination of Beleng leaf crude extract with Column Chromatography and Thin Layer Chromatography produced 15 fractions of compound, the fraction number VI which is made of three compounds with Rf value : 0.35; 0.55 and 0.78 efectively inhibited the growth of F. solani var. coeruleum on PDA medium.